Gas around galaxy haloes – III: hydrogen absorption signatures around galaxies and QSOs in the Sherwood simulation suite. Issue 2 (23rd January 2017) - Meiksin, Avery; Bolton, James S.; Puchwein, Ewald
Abstract: Modern theories of galaxy formation predict that galaxies impact on their gaseous surroundings, playing the fundamental role of regulating the amount of gas converted into stars. While star-forming galaxies are believed to provide feedback through galactic winds, quasi-stellar objects (QSOs) are believed instead to provide feedback through the heat generated by accretion on to a central supermassive black hole. A quantitative difference in the impact of feedback on the gaseous environments of star-forming galaxies and QSOs has not been established through direct observations. Using the Sherwood cosmological simulations, we demonstrate that measurements of neutral hydrogen in the vicinity of star-forming galaxies and QSOs during the era of peak galaxy formation show excess Ly α absorption extending up to comoving radii of ∼150 kpc for star-forming galaxies and 300–700 kpc for QSOs. Simulations including supernovae-driven winds account for the absorption around star-forming galaxies but not QSOs.